2011
DOI: 10.2164/jandrol.109.009258
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Saphenofemoral Insufficiency in Primary Adult Varicocele

Abstract: The aim of this study was to evaluate the possible relationship between varicocele and saphenofemoral insufficiency in patients diagnosed with primary varicocele. A total of 70 patients with the primary diagnosis of varicocele were included into the study. A total of 30 age-matched healthy adults were also included in the study as a control group. Varicocele was diagnosed by palpation and observation of each spermatic cord in standing position before and during a valsalva maneuver. Additionally, scrotal Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
3
20
1
Order By: Relevance
“…Approximately 15% of adult males suffer from clinical varicocoele, and 50–80% of these males have subclinical varicocoele (Zini et al ., ). Several theories have been proposed to explain the adverse effects of varicocoele, which include reduced homolateral testicular volume, impaired sperm production ranging from oligozoospermia to complete azoospermia and reduced fertility (Zini et al ., ; Benoff & Gilbert, ; Jarow, ; Marmar, ; Naughton et al ., ; Koyuncu et al ., ). However, how varicocoele affects spermatogenesis in the testis is poorly understood despite considerable research in this area (Balci et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Approximately 15% of adult males suffer from clinical varicocoele, and 50–80% of these males have subclinical varicocoele (Zini et al ., ). Several theories have been proposed to explain the adverse effects of varicocoele, which include reduced homolateral testicular volume, impaired sperm production ranging from oligozoospermia to complete azoospermia and reduced fertility (Zini et al ., ; Benoff & Gilbert, ; Jarow, ; Marmar, ; Naughton et al ., ; Koyuncu et al ., ). However, how varicocoele affects spermatogenesis in the testis is poorly understood despite considerable research in this area (Balci et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…1 Canales et al reported that the prevalence of varicocele in elderly men was greater than that of young control subjects. 2 However, our previous study showed that there are more newly-diagnosed cases of varicocele in patients aged 19-39 years compared with other age groups. 3 Subjects in this age group might have a higher rate of fertility problems and more chance of strenuous exercise, and are therefore more likely to seek medical attention, and older men do not care as much about the fertility issue and might have a higher incidence of asymptomatic varicocele.…”
Section: Author's Reply Response To Editorial Comments To Varicocele mentioning
confidence: 87%
“…However, the association between varicose veins and varicocele is still controversial. Koyuncu et al 2 and Kilic ß et al 1 showed that the prevalence of peripheral varicose veins was significantly higher in patients with varicocele than those without varicocele. In contrast, in a study of 100 participants, Yazici et al found no statistical relationship between the two conditions.…”
mentioning
confidence: 97%
“…In another series performed in 70 adult varicocoele patients and 30 age‐matched healthy controls, Koyuncu et al. [11] reported a statistically significant relation between varicocoele and SFJ insufficiency and suggested that this proposition must be evaluated with larger series to confirm the possible relation between these two pathological conditions.…”
Section: Discussionmentioning
confidence: 99%